Investigation of virtual collaborative learning environment - Lipeikienė, Joana; Pinkevičiūtė, Ingrida (Lietuvos matematikos rinkinys, 2003)
One form of virtual learning environments – collaborative learning environments has been investigated and are discussed in the paper. Fle3 software was used to create the learning environments for teaching informatics in a secondary school and for teaching computer math systems at the Vilnius Pedagogical University. The results of the research – summation of the learning process and analysis of learners’ answers to the questionnaire about Fle3 learning environment showed that the new forms of teaching are possible useful way of contemporary education.